Placement of SpaceOAR hydrogel spacer for prostate cancer patients treated with iodine‐125 low‐dose‐rate brachytherapy. (6th October 2019) - Morita, Masashi; Fukagai, Takashi; Hirayama, Kidai; Yamatoya, Jin; Noguchi, Tetsuo; Ogawa, Yu; Igarashi, Atsushi; Niiya, Akifumi; Kato, Masako; Morota, Madoka; Oshinomi, Kazuhiko; Ogawa, Yoshio; et al.
Abstract : Objectives: The aim of the present study was to report on our early experience with hydrogel spacer (SpaceOAR) placement in combination with iodine‐125 low‐dose‐rate brachytherapy for prostate cancer. Methods: From April 2018, SpaceOAR hydrogel spacer was placed in 100 consecutive patients undergoing iodine‐125 low‐dose‐rate brachytherapy. Complications and the status of the placement were evaluated. Deformation of the prostate by the spacer was examined measuring prostate diameters and evaluating the change from preoperative status. The position of the prostate was similarly examined by evaluating the change in distance between the pubic symphysis and the prostate. Post‐plan dosimetric data were compared with 200 patients treated without a spacer. Results: No complications were found during either the intraoperative or perioperative periods. The mean displacement distance of 11.64 mm was created, the mean value before spacer placement was 0.28 mm ( P  < 0.0001). The change of the prostate diameters showed a positive increase in all directions, with no significant negative change in any one direction. Regarding the change in distance between pubic symphysis and the prostate, no significant shortening trend was observed between the two groups ( P  = 0.14). Whereas the dosimetric parameters showed means of 0.001 and 0.026 cc for RV150 and RV100 in the spacer group, they were 0.025 and 0.318 cc, respectively, in the non‐spacer group, showing a significant decrease in both parameters ( P  < 0.001). Conclusions: Prostate deformation secondary to hydrogel placement might adversely affect dosimetric parameters in patients undergoing low‐dose‐rate brachytherapy. However, a significant reduction in the rectal dose can be adopted without adversely affecting the other parameters related to treatment outcome.